Bone scan images dataset for study of bone metastases in adult breast cancer patients at IICS-UNA, ParaguayZenodo - Carolina Elizabeth Villegas-Colmán; Julio César Mello-Román; José Luis Vázquez Noguera; Horacio Legal-Ayala; Pastor Pérez Estigarribia; Benicio Grossling-Vallejos; Ronald Rivas; María Gloria Pedrozo; Cynthia Duarte; Graciela Giménez; Andrés Uldera; Marina Arnal; et al. (Data in Brief)
This article presents 582 bone scan images from 291 adult patients who attended the Nuclear Medicine Service at the Instituto de Investigaciones en Ciencias de la Salud (IICS) of the Universidad Nacional de Asunción (UNA), Paraguay, between 2020 and 2024. The images were acquired using trimodal SPECT-CT-PET equipment, model AnyScan SCP, and the MEDISO brand. Approximately 20 mCi of technetium-99m methylene diphosphonate (99mTc-MDP) was administered to each patient, producing whole-body planar images in anterior and posterior projections of the axial and appendicular skeleton with a resolution of 256 × 1024 pixels. The images were labeled according to the final diagnosis by a nuclear physician, covering conditions ranging from joint lesions to bone metastases. This dataset will be helpful for researchers working on bone scan image analysis using artificial intelligence techniques to classify bone metastases.